Synthesis and Evaluation of 3D Nitrogen Doped Reduced Graphene Oxide (3D N@rGO) Macrostructure for Boosted Solar Driven Interfacial Desalination of Saline Water - Fisseha A Bezza; Samuel A. Iwarere; Shepherd M. Tichapondwa; Hendrik G. Brink; Michael O. Daramola; Evans MN Chirwa (Global Challenges)
Abstract Recently, there has been a growing interest in solar‐driven interfacial desalination technology, which focuses on the localization of heat to the air‐water interface. In this study, 3D nitrogen‐doped reduced graphene oxide (3D N@rGO) photothermal material is synthesized with a facile one‐step hydrothermal process. The material exhibited richer porosity, high hydrophilicity for efficient water channeling, and all‐directional solar absorption potential. The 3D N@rGO solar absorber attained up to ≈55 °C surface temperature rise and showed ≈134% photothermal conversion efficiency with 1.94 kg m−2 h−1 net freshwater generation rate under 1 sun solar illumination, owing to efficient latent heat recycle. On a high salinity desalination study performed using 10 and 20 wt.% salinity levels, the photothermal material showed 1.66 and 1.31 kg m−2 h−1 evaporation rates respectively. It sustained stable long‐term desalination performance without visible salt accumulation on the surface up to a salinity level of 10 wt.%. In a three‐day outdoor test carried out utilizing simulated seawater with a 3.5 wt.% NaCl solution, the 3D evaporator demonstrated an average freshwater production rate of 2.61 kg m−2 h−1, during the test the solar power density reached up to 1.1 kW m−2. The 3D solar absorber exhibited a promising potential for large‐scale seawater desalination in water‐scarce regions worldwide.